Analisis Kesalahan dan Tanda Baca Teks Berita pada Surat Kabar Kompas Edisi Januari 2024 sebagai Kalayakan Bahan Bacaan dan Sumber Informasi - Auliana Fathiya Hanim; Fathiya Salama; Lingga Dwi Andika; Ulya Fadhilatur Rohmah; Asep Purwo Yudi Utomo; Rossi Galih Kesuma; Nur Indah Wahyuni (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
This research reviews various spelling and punctuation errors, with a focus on the analysis of language errors which include the use of language that does not comply with the rules that have been established based on grammar standards. Similar errors were still found in the January 2024 edition of the Kompas Daily Letter, especially regarding the use of language and punctuation. The aim of this research is to analyze language and punctuation errors contained in the January 2024 Edition of the Kompas Newspaper. The approach used is a qualitative and descriptive approach, which aims to describe the findings in the form of word and sentence analysis. The data analysis technique used is listening and taking notes. The results of the research and discussion regarding the analysis of spelling and punctuation errors in the January 2024 edition of Kompas news were carried out by reading and understanding the content of the news. Then, the researcher marked sentences that contained spelling and punctuation errors, and grouped the marked data for analysis. Conclusions based on the results of the analysis of spelling and punctuation errors when reading the news in the January 2024 edition of the Kompas Newspaper were prepared after carrying out the analysis process. This research data was collected by reading and understanding the content of the news, then marking sentences that contained spelling errors. The data is then analyzed to find errors in various aspects, such as spelling, morphology, semantics and syntax. It is hoped that the benefits of this research can be a reference and increase insight in learning to use spelling and punctuation correctly according to the Big Indonesian Dictionary.